The Legitimacy of Circular Letter in Handling COVID-19 Pandemic: Legitimasi Surat Edaran dalam Penanganan Pandemi COVID-19 - Disantara, Fradhana Putra (Rechtsidee, 2020)
The purpose of this legal research is to analyze the relevance of the discretion of government officials during the COVID-19 pandemic with the concepts and legislation related to legal issues; as well as analyzing the existence of a Circular to legitimize the handling of COVID-19 with statutory regulations. This legal research is carried out by making an inventory of various primary and secondary legal materials, so as to obtain relevant and critical studies of the legal issues discussed. The results of this legal research are that the discretion made by government officials can be justified legally if it is relevant to several provisions contained in legislation for the realization of good emergency governance; and the existence of a circular letter is legally valid if it is in accordance with the laws and regulations and the General Principles of Good Governance, by understanding that a circular is not a product of rules that are in the order of national legislation. Thus, a circular does not have strong and binding legal legitimacy. Therefore, the researcher recommends the criteria and classification of the parameters of discretion in the form of a circular as outlined in the form of a Supreme Court Regulation. This should be done so that there is no abuse of authority in implementing discretionary power by government officials and general legal principles.